Multistage switched inductor boost converter for renewable energy application - Maroti P.K.; Padmanaban S.; Bhaskar M.S.; Blaabjerg F.; Ramachandaramurthy V.K.; Siano P.; Fedk V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inductors; Energy conversion; Gain measurement; MATLAB; Metals; Semiconductor devices; BOOST converter; High voltage gain; Multistage converters; Renewable energies; Switched inductors; DC-DC converters